БОЛАЖАҚ МУҒАЛЛИМЛЕРДИҢ КӘСИПЛИК-ГНОСТИКАЛЫҚ КОМПЕТЕНТЛИГИН ҚӘЛИПЛЕСТИРИЎ ПРИНЦИПЛЕРИ - Бекниязов, Қ.И. (FAN va JAMIYAT, 2025)
The article examines the principles of forming future teachers' professional-gnostic competence as a key component of their professional training. The theoretical foundations of this type of competence are analyzed furthermore, there is given its structure, and significance in pedagogical activity. The author emphasizes the need to introduce innovative teaching methods aimed at developing analytical and research skills in future teachers.